2021
DOI: 10.5489/cuaj.7539
|View full text |Cite
|
Sign up to set email alerts
|

En bloc transurethral resection of bladder tumors: A review of current techniques

Abstract: Introduction: Growing interest surrounds the concept of en bloc transurethral resection of bladder tumors (ERBT). Theoretical advantages include improved adherence to oncological principles and potential yield of superior pathological specimens. Multiple ERBT methods exist. This review summarizes the current evidence regarding application of differing techniques and technologies to ERBT. Methods: A systematic review of MEDLINE/EMBASE/Scopus databases was performed, using terms “en bloc,” “ERBT,” “bladder,” and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In addition, this is also the rst case in which a complete tumor specimen was obtained through the urethra. Previous literature has reported that ERBT has the advantages of a lower surgical complication rate and higher quality of tumor specimens compared to conventional TURBT in bladder urothelial tumor surgery [18,19]. We believe that for non-muscle invasive bladder PEComa, especially solitary, with pedicle, narrow-basal, small-sized tumor, ERBT is a good surgical approach to resect the tumor to maintain tumor integrity, reduce intraoperative bleeding, and minimize tissue remnants.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, this is also the rst case in which a complete tumor specimen was obtained through the urethra. Previous literature has reported that ERBT has the advantages of a lower surgical complication rate and higher quality of tumor specimens compared to conventional TURBT in bladder urothelial tumor surgery [18,19]. We believe that for non-muscle invasive bladder PEComa, especially solitary, with pedicle, narrow-basal, small-sized tumor, ERBT is a good surgical approach to resect the tumor to maintain tumor integrity, reduce intraoperative bleeding, and minimize tissue remnants.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, ERBT has emerged as an alternative to cTURB [ 42 ]. In contrast to ‘piecemeal’ resection by cTURB, ERBT incorporates a more delicate en bloc sculpting and tumor excision [ 43 ]. ERBT appears safe, feasible, and effective with demonstrably higher rates of DM in the pathologic specimen and provides better staging [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transurethral resection of bladder tumors (TURBT) is a crucial procedure in the management of bladder cancer. The goals of TURBT are to make the correct diagnosis, sample the detrusor muscle for staging, and completely remove all visible lesions [ 1 , 2 , 3 , 4 , 5 ]. The quality of the resection strongly influences patient prognosis and overall treatment success.…”
mentioning
confidence: 99%
“…Although it is still the gold standard, conventional TURBT using the incision and scatter technique has a number of potential drawbacks. For example, thermal damage to nearby tissue can lead to difficulty in the pathological evaluation of fragmented tissue, and tumor fragmentation with a high number of exfoliated cancer cells could lead to infield and outfield recurrences [ 1 , 2 , 3 , 4 , 5 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation